Physical properties of coconut shell nanoparticles - Bellow, S. A.; Agunsoye, J. O.; Adebisi, J. A.; Kolawole, F. O.; Hassan, S. B. (Kathmandu University Journal of Science, Engineering and Technology, 2018)
Physical properties such as apparent density, bulk density, compressibility index and particle sizes of carbonized and uncarbonized coconut shell nanoparticles produced through top down approach have been studied. Percentage composition of the coconut fruit was determined using five different coconut fruit samples. Results revealed that coir occupies the highest percentage; coconut shells account for 15 % while the flesh and liquid occupy 30 % of the whole coconut fruit. The apparent densities of the uncarbonized and carbonized coconut shell nanoparticles obtained at 70 hours of milling are 0.65 g/cm3 and 0.61 g/cm3 respectively. Their respective compressibility indices and average particle sizes are 46.4 % and 69.7 %; 50.01 nm and 14.29 nm. The difference in the particle sizes of the carbonized and uncarbonized coconut shell nanoparticles can be linked with reduction in the moisture content and volatiles of the carbonized coconut shell nanoparticles due to carbonization process. The reduction in the moisture and volatiles results in the enhanced hardness and brittleness of the carbonized coconut shells which facilitate their breakage during the course of milling than that of the uncarbonized coconut shells. Kathmandu University Journal of Science, Engineering and Technology Vol. 12, No. I, June, 2016, Page: 63-79